Beliefs related to the return of the soul of the deceased to his native home in the traditional funeral and memorial rituals of the peoples of the North-West Caucasus (on the example of the Abkhazians and Karachays) - Ritsa Sh. Zelnitskaya (Кавказология, 2025)
The article is devoted to one element of the traditional funeral and memorial rituals among the peoples of the Northwest Caucasus (using the example of the Abkhazians and Karachays), associated with rituals and beliefs about the return of the soul of the deceased to his native home. According to popular beliefs, the soul of a person did not completely leave his family, clan and community, it remained a part of the person himself, embodying his own personality. All the rituals that were performed after a person’s death were aimed at ensuring that the soul did not need anything in the “next world” and stayed with previously departed relatives. Death among these peoples was perceived, on the one hand, as a tragic event, but on the other hand, they talked about it quite calmly and realized that people were temporarily in this world. The unexpected death of a person was especially tragically perceived. In the case when a person died outside the home or community space, it was necessary to perform appropriate rituals “to return the soul of the deceased to his native home in order to reunite it with his family,” so that it would not become lost and dangerous primarily for relatives. The rite given in the article as an example, associated with the resurrection of the soul of a drowned man, was similar among some peoples of the North-Western Caucasus.